From Octahedron Crystals to 2D Silicon Nanosheets: Facet‐Selective Cleavage and Biophotonic Applications. Issue 45 (20th October 2020) - Cheng, Ziqiang; Cui, Haodong; Xiao, Quanlan; Huang, Hao; Kang, Yihong; Liu, Qian; Wang, Jiahong; Chu, Paul K.; Yu, Xue‐Feng
Abstract: 2D silicon nanosheets (SiNSs) are promising materials for biomedicine but facile synthesis of SiNSs remains a challenge. Herein, by means of a sulfur‐iodine co‐assisted chemical vapor transport method, octahedron silicon (oct‐Si) crystals with fully exposed {111} planes are prepared as precursors for efficient synthesis of SiNSs by facet‐selective exfoliation. The 13 nm thick SiNSs have good biocompatibility and the sharp Raman scattering signal facilitates intracellular Raman imaging upon exposure to a near‐infrared (NIR) laser. Furthermore, the SiNSs have excellent NIR photothermal characteristics such as a large extinction coefficient of 11.3 L g −1 cm −1 and high photothermal conversion efficiency of 21.4% at 1064 nm. In vitro experiments demonstrate superior NIR‐II photothermal therapeutic effects in killing cancer cells. Comparing to conventional methods, the novel facet‐selective cleavage strategy is more controllable and environmentally friendly boding well for the fabrication of non‐van der Waals 2D materials. The multimodal photonic behavior also suggests large potential of the SiNSs pertaining to integrated multi‐NIR biophotonic techniques using single nanomaterials. Abstract : 2D silicon nanosheets (SiNSs) are synthesized by facet‐selective exfoliation of octahedron silicon crystals with fully exposed {111} planes. The SiNSs have good biocompatibility and the strong Raman signal enables efficient Raman imaging of cells. A high photothermal conversion capability upon 1064 nm laser irradiation is demonstrated to kill cancer cells efficiently.